Retrospective Analysis of Factors Influencing Clinical Outcomes of Revision Surgery for Periprosthetic Infection After Unicondylar Knee Arthroplasty - Cao X; Zhao Z; Zhang C; Gao B; Dong R; Ma L (Infection and Drug Resistance)
Xuyang Cao,1 Zizi Zhao,2 Cheng Zhang,3 Bo Gao,1 Ruifang Dong,2 Lijie Ma1 1Trauma Center, The Third Hospital of Hebei Medical University, Shijiazhuang, Hebei, People’s Republic of China; 2Department of Orthopedics, North China Medical and Health Group Xingtai General Hospital, Xingtai, Hebei, People’s Republic of China; 3Department of Orthopedics, The First Central Hospital of Baoding City, Baoding, Hebei, People’s Republic of ChinaCorrespondence: Lijie Ma, Trauma Center, The Third Hospital of Hebei Medical University, No. 102 Youyi North Street, Qiaoxi District, Shijiazhuang, Hebei, 050000, People’s Republic of China, Tel +86-17733299114, Email malijie305x@hebmu.edu.cnObjective: To identify factors influencing clinical outcomes of revision surgery for periprosthetic joint infection (PJI) after unicondylar knee arthroplasty (UKA).Methods: This retrospective study included 40 patients who underwent UKA revision for PJI (May 2009–May 2023). Patients were divided into responders (n=27, favorable outcomes: no infection, KSS ≥ 80, HSS ≥ 85 at 6 months) and non-responders (n=13, suboptimal outcomes: persistent infection or KSS < 80/HSS < 85). Inflammatory markers (CRP, WBC), Knee Society Score (KSS), and Hospital for Special Surgery (HSS) score were assessed. Multivariate logistic regression identified predictors of success.Results: Non-responders had higher rates of diabetes (46.2% vs 14.8%), smoking (30.8% vs 18.5%), alcohol use (23.1% vs 14.8%), Gram-positive infections (30.8% vs 11.1%), and deep infections (84.6% vs 22.2%, all P< 0.05). Key predictors of success included optimal antibiotic management (OR=1.33, 95% CI=1.02– 1.74), patient compliance (OR=1.44, 95% CI=1.08– 1.92), and absence of diabetes (OR=1.54, 95% CI=1.24– 1.98), smoking (OR=1.60, 95% CI=1.08– 2.37), or Gram-positive infections (OR=1.46, 95% CI=1.12– 1.90, all P< 0.05).Conclusion: Diabetes, smoking, alcohol use, Gram-positive infections, deep infection, antibiotic management, and compliance significantly impact UKA revision outcomes. Smoking showed the strongest association (OR=1.60). Clinicians should prioritize preoperative optimization (glycemic control, smoking cessation) and protocol-driven antibiotic use. Findings are exploratory due to small sample size and require validation in larger cohorts.Keywords: unicondylar knee arthroplasty, periprosthetic infection, revision surgery, clinical outcomes, influencing factors